2017
DOI: 10.1016/j.neuron.2017.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Direct Dopaminergic Projections from the SNc Modulate Visuomotor Transformation in the Lamprey Tectum

Abstract: Dopamine neurons in the SNc play a pivotal role in modulating motor behavior via striatum. Here, we show that the same dopamine neuron that targets striatum also sends a direct branch to the optic tectum (superior colliculus). Whenever SNc neurons are activated, both targets will therefore be affected. Visual stimuli (looming or bars) activate the dopamine neurons coding saliency and also elicit distinct motor responses mediated via tectum (eye, orienting or evasive), which are modulated by the dopamine input.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 48 publications
(70 reference statements)
2
71
0
Order By: Relevance
“…The lamprey homolog of the SNc/VTA, the nucleus of the posterior tuberculum, is located in the caudal diencephalon (Figure 1A) and contains dopaminergic neurons ( Figure 1B) that target striatum [13]. These striatum-projecting neurons send collaterals to brainstem motor-related centers, including the optic tectum and mesencephalic locomotor region (MLR) [1,3,14,15]. The SNc/VTA can be clearly differentiated from the cerebrospinal fluid-contacting (CSF-c) dopaminergic neurons in the mammillary area, which are significantly smaller (8.9 ± 1.2 mm, n = 240; versus 13.0 ± 2.8 mm, n = 182 in SNc/VTA; Student's t test, p < 0.01; Figure 1B), and neither project to striatum nor to tectum.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lamprey homolog of the SNc/VTA, the nucleus of the posterior tuberculum, is located in the caudal diencephalon (Figure 1A) and contains dopaminergic neurons ( Figure 1B) that target striatum [13]. These striatum-projecting neurons send collaterals to brainstem motor-related centers, including the optic tectum and mesencephalic locomotor region (MLR) [1,3,14,15]. The SNc/VTA can be clearly differentiated from the cerebrospinal fluid-contacting (CSF-c) dopaminergic neurons in the mammillary area, which are significantly smaller (8.9 ± 1.2 mm, n = 240; versus 13.0 ± 2.8 mm, n = 182 in SNc/VTA; Student's t test, p < 0.01; Figure 1B), and neither project to striatum nor to tectum.…”
Section: Resultsmentioning
confidence: 99%
“…Dopaminergic neurons in the substantia nigra (SNc) innervate both striatum and the superior colliculus in mammals, as well as its homolog the optic tectum in lampreys, belonging to the oldest group of living vertebrates [1][2][3]. In the lamprey, we have previously shown that the same neuron sends axonal branches to both striatum and the optic tectum [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations